Aortic Sources of Embolism - Viedma-Guiard, Elena; Guidoux, Celine; Amarenco, Pierre; Meseguer, Elena (Frontiers in Neurology, 2021)
Aortic arch atheroma is a frequent finding in ischemic stroke patients. It is often a marker of atherosclerosis. However, in some cases, it might be considered a source of cerebral emboli. Transesophageal echography is considered the gold standard for its detection, whereas computed tomography angiography could also be a good alternative. Despite the interest for its pathology, no specific treatment has been defined and, in these patients we should follow the general guidelines for prevention of atherosclerotic disease. This review aims to offer guidance on patients with aortic arch atheroma, about its casual role in stroke, diagnosis and treatment based on current available evidence.